TINGKAT DOMINANSI DAN ASOSIASI KELOMPOK KAYU INDAH DI AREAL IUPHHK-HTI PT. BHATARA ALAM LESTARI KABUPATEN MEMPAWAH - Zulkifli, M; Herawatiningsih, Ratna; Yani, Ahmad (Universitas Tanjungpura, 2018)
This study aims to assess and provide information on how big the dominance and association of trees in IUPHHK-HTI PT. Bhatara Alam Lestari area. The problem in this research is the existence of human activities in managing the forest excessively, the forest was converted to a lot of plantations and agricultural areas and the occurrence of illegal forest clearing, feared loss of forest vegetation in the area. The research method used was plotted path mixed method with the laying of the purposive sampling path, the observation variable was the entire growth rate of the seedling, stake, pole, and tree levels. Based on the results of research there were 51 species of trees, 7 species of which were trees that entered into the group of Kayu Indah. Based on the results of research conducted it could be concluded that the type of dado, embun, jungkang, kayu malam and ubah were the dominant vegetation type for seedling level. Type of embun, jungkang, kayu malam, medang, nyatoh and ubah were the dominant vegetation type for stake level. Type of dado, embun, jungkang, kempas, petai, rengas and ubah were the dominant vegetation type for pole level. Type of jungkang, kayu malam, medang, ubah were the dominant tree for tree level. While the Ochiai index of kayu malam species had a negative relationship to the 3 dominant tree species, because the value of the Ochiai index was closed to 0.Keywords: Association, Dominance, Kayu Indah, Secondary Forest.